2016
DOI: 10.5047/agbm.2016.00601.0001
|View full text |Cite
|
Sign up to set email alerts
|

Plant Polyphenols as a Double-Edged Sword in Health Promotion: Lessons from the Experimental Models Using Simple Phenolic Acids

Abstract: erized molecules such as tannins are reportedly identified. Phenolic acids include caffeic acid, vanillic acid, and coumaric acid, that account for approximately onethird of the total dietary intake of polyphenols. Flavonoids, account for the remaining two-thirds of polyphenol intake, can be further subdivided into 13 classes, including flavones, flavanones, flavonols, isoflavones, catechins (flavanols), anthocyanins and proanthocyanidins, with more than 5,000 identified compounds. Epidemiological studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 172 publications
(226 reference statements)
1
4
0
Order By: Relevance
“…EGCg has been reported to easily undergo autoxidation at alkaline pH, which is accompanied by the generation of hydrogen peroxide . As shown in Figure A, 10 μM of EGCg, which completely inhibited the ACE activity (Figure B), produced 16.1 μM of hydrogen peroxide during a 30‐min incubation.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…EGCg has been reported to easily undergo autoxidation at alkaline pH, which is accompanied by the generation of hydrogen peroxide . As shown in Figure A, 10 μM of EGCg, which completely inhibited the ACE activity (Figure B), produced 16.1 μM of hydrogen peroxide during a 30‐min incubation.…”
Section: Resultssupporting
confidence: 90%
“…EGCg has been reported to easily undergo autoxidation at alkaline pH, which is accompanied by the generation of hydrogen peroxide. [14,18] As shown in Figure 3A…”
Section: Hydrogen Peroxide Was Not Involved In the Ace Inhibition By mentioning
confidence: 99%
See 1 more Smart Citation
“…( 1 ) For example, both BITC and PEITC promote urinary bladder chemical carcinogenesis in rats, possibly through necrotic cytotoxicity by severe protein modification. ( 87 ) Our previous studies on the toxic effects of higher doses of phenolic acids ( 88 ) also support this idea. If the dose employed is higher than that required for health promotion, the benefitial effects of ITCs might not be entirely expected.…”
Section: Discussionmentioning
confidence: 57%
“…Research reported that dietary polyphenols may activate AMPK (AMP-activated protein kinase) via SIRT1 and LKB1, thus inhibiting ACC activity and decreasing the production of malonyl-CoA. As a result, FA β-oxidation is upregulated along with downregulated FA synthesis, thereby leading to hepatocyte lipid reduction [ 36 ]. In the present experiment, the dietary strawberry extract, irrespective of the dosage, exerted similar antioxidative and anti-inflammatory effects in the liver and plasma of rats fed an HFD.…”
Section: Discussionmentioning
confidence: 99%